Perjuangan Warganet Indonesia Melawan Genosida Israel terhadap Palestina melalui Tindak Tutur Deklaratif pada Media Sosial Twitter - Isna, Fariha Nurul; Mumtaz, Tsabitah Zain; Setyawati, Eti; Wahyuni, Lilik (Multiverse: Open Multidisciplinary Journal, 2023)
The ongoing Palestine-Israel conflict has garnered attention from Indonesian netizens, particularly on Twitter. Indonesian users actively express their support for Palestine, reflecting a commitment to sustainable development goals, notably human rights advocacy. This defense is evident in historical posts and comments on Twitter, portraying declarative illocutionary speech acts. Employing qualitative descriptive methods, this research analyzes the data to unveil the form and function of these speech acts. The pragmatic approach involves classifying context and cotext, providing a comprehensive understanding of the speech acts' nuances and functions in the given discourse. This study contributes to the exploration of Indonesian netizens' reactions and activism concerning global issues.